2006
DOI: 10.1007/s11270-005-9069-7
|View full text |Cite
|
Sign up to set email alerts
|

Concentration Of Trace Elements in Airborne PM10 from Jobos Bay National Estuary, Puerto Rico

Abstract: Atmospheric suspended particulate matter (PM 10 ) was sampled from the Jobos Bay estuary in Salinas and from a reference site (Fajardo) in the east coast of Puerto Rico. Salinas is a town in the south coast of Puerto Rico adjacent to a number of industries and to the only coal power plant on the island. It is important to study the air quality in this area since significant releases of metal to the environment due to energy production could represent a threat to local communities. This study evaluated the leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…These studies have demonstrated that PM 10 fractions collected from Puerto Rican urban areas (e.g., Guaynabo, Salinas) contained higher concentrations of ENX and TMET, respectively (e.g., Cd, Cu, Fe, Ni, Hg, Pb and V) than extracts collected from rural coastal regions (e.g., Fajardo) and were significantly toxic to in vitro systems [12,22,62]. Subsequent work also demonstrated that PM 2.5 fractions collected from indoor areas contained higher concentrations of these metals than PM samples obtained from outdoor areas, causing significant release of pro-inflammatory cytokines in vitro [64-68]. These results suggest that PM 2.5 and PM 10 fractions and some of their constituents (e.g., ENX and TMET) present at different Puerto Rican locations (urban and rural areas) may play a key role in the exacerbation of certain respiratory diseases (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…These studies have demonstrated that PM 10 fractions collected from Puerto Rican urban areas (e.g., Guaynabo, Salinas) contained higher concentrations of ENX and TMET, respectively (e.g., Cd, Cu, Fe, Ni, Hg, Pb and V) than extracts collected from rural coastal regions (e.g., Fajardo) and were significantly toxic to in vitro systems [12,22,62]. Subsequent work also demonstrated that PM 2.5 fractions collected from indoor areas contained higher concentrations of these metals than PM samples obtained from outdoor areas, causing significant release of pro-inflammatory cytokines in vitro [64-68]. These results suggest that PM 2.5 and PM 10 fractions and some of their constituents (e.g., ENX and TMET) present at different Puerto Rican locations (urban and rural areas) may play a key role in the exacerbation of certain respiratory diseases (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…For acid extraction, filters were digested by adding nitric acid and ultra pure water. It was conducted on a hot plate, heated and refluxed at 908C + 58C for 2 h (Gioda et al 2006). …”
Section: Methodsmentioning
confidence: 99%
“…US EPA methods 202.2, 7060A, 7131A, 7381, 7421, 7521 and 7911 were used for the particular analyses of Al, As, Cd, Fe, Pb, Ni and V, respectively (US EPA 1986–1996). Detailed metal analyses were described elsewhere (Gioda et al 2006). …”
Section: Methodsmentioning
confidence: 99%
“…Also, for PTFE filters, an extraction procedure has been proposed at room temperature with a mixture of HF:HNO 3 [61,83], although the extraction time is long (4 days), in comparison to the few hours employed with methodologies that heat the sample (e.g. extraction with HNO 3 on a heating plate for 2 h, as described by Gioda et al [85]. A faster extraction procedure for quartz fibre filters has been employed by Yadav and Turner [86] which consists of the extraction with a mixture of HNO 3 :HCl in a heating block at 90 ºC for 90 min.…”
Section: Sample Single Step Extractionmentioning
confidence: 99%
“…The authors indicated that the trueness of their study provided values in the range of 99.6 to108.2 % for all the metals, compared to the certified values. Gioda et al [85] has employed NIST SRM 2583 Indoor Dust, with a 76% recovery of the As certified value.…”
Section: Qa/qc For Total As Determinationmentioning
confidence: 99%